Глава 8. Забезпечення доказів у цивільному судочинстві: історія, теорія і практика - Тимченко , Геннадій Петрович (Цивільний процес: теорія і практика. Концепції вчених з удосконалення законодавства про цивільне судочинство. Монографія, 2023)
The chapter is devoted to the study of the procedure for securing of evidence in civil proceedings.The author notes that the problems of evidence proving and know ledge are among the key issues for civil procedural science in the entire history of its continuous formation and development. The current stage of the evolution of civil procedural thought in this sense is not an exception. Domestic legal scholars also continue to address the basic concepts and categories of evidentiary law, the principles of normative regulation of evidentiary activity, problematic issues of its implementation in various proceedings and stages of the judicial process. Given the general direction of the collective monographic study, we dwell only on some common or debatable issues of the functioning of the institution of securing evidence in civil proceedings.The researcher analyses the stages of formation of the first ideas regarding the provision of evidence in civil proceedings and the legal sources of the periods of development of Ukrainian statehood.Considering the place of the rules for securing evidence in the structure of proving the circumstances of civil cases, the author substan tiates that the functional principles of the civil process are the basis of the evidentiary activity, among which it is customary to highlight the principles of competition, discretionary and procedural equality of the parties. These principles not only determine the scope of rights and obligations of the parties, but also, they guarantee the ensuring of the right to a fair trial. Procedures for securing evidence are an important element of the mechanism for implementation the parties’ evidentiary rights, in particular the right to collect and submit evidence, since the necessary evidence is not always at the disposal of the parties due to various circumstances. At the same time, the possibility of securing evidence corresponds to the general duty of the court as regarding the judicial management of the process.The securing of evidence in civil proceedings is considered in the work as an activity of the parties aimed at obtaining the necessary evidence in compliance with the conditions stipulated by law and as an activity of the court, which helps in the collection and submission of evidence.Articles 116-119 of the Civil Procedural Code of Ukraine are devoted to the procedures for securing of evidence in domestic civil procedural legislation. They regulate the requirements for the form and content of the application for the provision of evidence, the conditions and time for submitting such an application, the procedure for consideration of this issue, and a number of others things.It is noted that the legislator, regulating many aspects of the procedure for securing of evidence (time frames for submitting such an application, features of court proceedings and the consequences of initiating securing of evidence issues), sees its implementation exclusively in action proceedings.The researcher analyses the peculiarities of the procedure for secu ring testimony of witnesses, written, physical and electronic evidence.